Effect of electrospark doping on mechanical properties of Al-Si-Cu alloys - N. E. Fomin; I. Kh. Khasan; V. M. Kyashkin (Advanced Engineering Research)
Introduction. Microhardness and wear resistance of the aluminum alloy (AK5M7) after its surface treatment through electrospark doping (ESD) using A (Cu) and P (Cu+P) electrodes with different applied energy is considered. The work objective is to study the relationship of the physicomechanical and strength properties of the surface of AK5M7 alloy obtained after ESD with copper and copper-phosphorus electrodes.Materials and Methods. X-ray diffraction and X-ray fluorescence analysis methods were used to determine the phase composition, coherent-scattering regions (CSR), and the surface microstrain.Research Results. It is established that with increasing energy, the values of microhardness and wear resistance increase when using both electrodes. The sample was modified by P electrode with the energy of 0.79 J. In this case, the maximum value of microhardness increased 5.3 times, wear resistance -1.6 times. It is found that with ESD, new intermetallic phases of Al2Cu and Cu3P are formed on the surface of the alloy under study. If the value of the energy used is maximum (0.79 J), the concentration of the Al2Cu phase increases 5 and 9 times with A and P electrodes, respectively, and the concentration of the Cu3P phase increases more than 4 times when using P electrode. The experimental data obtained suggest size reduction of the CSR and an increase in the microstrain values for all the Al, Al2Cu, and Cu3P phases on the surface.Discussion and Conclusions. An increase in energy with the ESD involves an increase in the defective factors and a change in the phase composition of the newly obtained surfaces. This may explain the increase in wear resistance of the surface.